Effects of tissue handling and processing steps on PCR for detection of Mycobacterium tuberculosis in formalin-fixed paraffin-embedded samples - Barcelos, Denise; Franco, Marcello F.; Leão, Sylvia Cardoso (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
Development and standardization of reliable methods for detection of Mycobacterium tuberculosis in clinical samples is an important goal in laboratories throughout the world. In this work, lung and spleen fragments from a patient who died with the diagnosis of miliary tuberculosis were used to evaluate the influence of the type of fixative as well as the fixation and paraffin inclusion protocols on PCR performance in paraffin embedded specimens. Tissue fragments were fixed for four h to 48 h, using either 10% non-buffered or 10% buffered formalin, and embedded in pure paraffin or paraffin mixed with bee wax. Specimens were submitted to PCR for amplification of the human beta-actin gene and separately for amplification of the insertion sequence IS6110, specific from the M. tuberculosis complex. Amplification of the beta-actin gene was positive in all samples. No amplicons were generated by PCR-IS6110 when lung tissue fragments were fixed using 10% non-buffered formalin and were embedded in paraffin containing bee wax. In conclusion, combined inhibitory factors interfere in the detection of M. tuberculosis in stored material. It is important to control these inhibitory factors in order to implement molecular diagnosis in pathology laboratories.